Response of Ugandan common bean varieties to Pseudocercospora griseola and Angular leaf spot disease development in varietal mixtures - Olango, N; Tusiime, G; Mulumba, J. W.; Nankya, R; Fadda, C; Jarvis, D. I.; Paparu, P (Taylor & Francis, 2017)
Angular leaf spot (ALS) is one of the most economically important bean diseases in Africa. One promising control option for the disease is the use of mixtures of resistant and susceptible varieties. This research evaluated (1) the reaction of farmer preferred bean varieties to ALS in the screenhouse and on-station and (2) the effect of different spatial arrangements of resistant and susceptible bean varieties on ALS disease development. For the latter, ﬁve mixture combinations and two controls were laid out in a Randomized Complete Block Design having three replicates. Analysis of variance and least signiﬁcant differences (LSDs) were used to compare disease levels in both studies above. Varietal screening showed signiﬁcant differences in varietal reaction to ALS. Screenhouse disease scores ranged between 0 and 5, compared to 0.7–3.9 in the ﬁeld. For the varietal mixture trial, the lowest disease levels and the highest mixture efﬁciencies were observed for the combination of equal proportions of the susceptible and resistant varieties randomly mixed (even mixture) prior to planting. We conclude that even mixtures reduce the amount of ALS disease that develops in the season.
Keywords: Pseudocercospora griseola; Angular leaf spot disease; Varietal mixtures